Septic Shock Nonsurvivors Have Persistently Elevated Acylcarnitines Following Carnitine Supplementation. Issue 4 (April 2018) - Puskarich, Michael A.; Evans, Charles R.; Karnovsky, Alla; Das, Arun K.; Jones, Alan E.; Stringer, Kathleen A.
ABSTRACT: Introduction: Sepsis-induced metabolic disturbances include hyperlactatemia, disruption of glycolysis, protein catabolism, and altered fatty acid metabolism. It may also lower serum L-carnitine that supports the use of L-carnitine supplementation as a treatment to ameliorate several of these metabolic consequences. Methods: To further understand the association between L-carnitine-induced changes in serum acylcarnitines, fatty acid metabolism and survival, serum samples from (T0), 12 hfollowing completion (T24) of L-carnitine (n = 16) or placebo (n = 15) administration, and 48 h (T48) after enrollment from patients with septic shock enrolled in a randomized control trial were assayed for acylcarnitines, free fatty acids, and insulin. Data were analyzed comparing 1-year survivors and nonsurvivors within treatment groups. Results: Mortality was 8 of 16 (50%) and 12 of 15 (80%) at 1 year for L-carnitine and placebo-treated patients, respectively. Free carnitine, C2, C3, and C8 acylcarnitines were higher among nonsurvivors at enrollment. L-Carnitine treatment increased levels of all measured acylcarnitines; an effect that was sustained for at least 36 h following completion of the infusion and was more prominent among nonsurvivors. Several fatty acids followed a similar, though less consistent pattern. Glucose, lactate, and insulin levels did not differ based on survival or treatment arm. Conclusions: In human patients with septic shock, L-Carnitine supplementation increases a broad range of acylcarnitine concentrations that persist after cessation of infusion, demonstrating both immediate and sustained effects on the serum metabolome. Nonsurvivors demonstrate a distinct metabolic response to L-carnitine compared with survivors, which may indicate preexisting or more profound metabolic derangement that constrains any beneficial response to treatment. Abstract : Supplemental Digital Content is available in the text